2014
DOI: 10.1111/cas.12489
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide‐binding protein 1 is one of the key molecules contributing to cancer cell radioresistance

Abstract: Standard fractionated radiotherapy for the treatment of cancer consists of daily irradiation of 2-Gy X-rays, 5 days a week for 5–8 weeks. To understand the characteristics of radioresistant cancer cells and to develop more effective radiotherapy, we established a series of novel, clinically relevant radioresistant (CRR) cells that continue to proliferate with 2-Gy X-ray exposure every 24 h for more than 30 days in vitro. We studied three human and one murine cell line, and their CRR derivatives. Guanine nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The role of GBP1 in EOC is controversial. On the one hand, GBP1 over-expression has been associated with chemo-resistance [32,33], through a PIM1-mediated interaction [34]. In addition, Wadi et al, reported that higher GBP1 gene expression, detected by microarray technology, correlated with poorer progression-free survival, in a set of ovarian cancer patients with optimal tumor debulking and treated with platinum + taxol chemotherapy [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of GBP1 in EOC is controversial. On the one hand, GBP1 over-expression has been associated with chemo-resistance [32,33], through a PIM1-mediated interaction [34]. In addition, Wadi et al, reported that higher GBP1 gene expression, detected by microarray technology, correlated with poorer progression-free survival, in a set of ovarian cancer patients with optimal tumor debulking and treated with platinum + taxol chemotherapy [52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inducible expression of GBP1 in mouse mammary adenocarcinoma TS/A cells inhibited their in vivo growth in syngeneic mice, predominantly through inhibition of angiogenesis [26]. Nevertheless, GBP1 expression may correlate with aggressive behavior in other cancers, including esophageal carcinoma [30] or glioblastoma [31], or with radio-or chemo-resistant phenotypes in different tumor cell types, including ovarian and head and neck carcinoma [32][33][34]. Here, we show that IL-27 or IFN-γ stimulated the release of full-length GBP1 in vitro, through non-classical secretory pathways, in the human EOC cell lines SKOV3 and OVCAR5 and in primary culture A161.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian and head-and-neck cancers, however, GBP1 has been consistently associated with disease progression and the development of treatment resistance (17,60). This trend was first noted in profiling of human ovarian cancer cell lines, which found that high GBP1 expression strongly correlated with paclitaxel resistance and that its knock-out restored treatment sensitivity (60,61). These findings have been borne out in examination of patient samples, where, in a separate paper, Wadi et al (62) replicated previous findings of GBP1's sufficiency to protect against paclitaxel-mediated apoptosis and also found high GBP1 expression in 17% of pre-treatment ovarian cancer patients.…”
Section: Gbp1 In Cancermentioning
confidence: 99%
“…The immune and tumor related nature of these three genes are supported by the following published data: (i) IFI30 suppresses mouse primary T cell reactivity in vitro and mouse autoimmunity through cellular redox chemistry and ERK1/2 phosphorylation in vivo, promotes cell proliferation of a glioma cell line, but IFI30 RNA has been associated, with better patient survival rate in breast cancer and diffuse large B cell lymphoma (DLBCL) (9-14), (ii) GBP1 suppresses TCR signaling through lymphocyte cell-specific protein-tyrosine kinase and IL2 production in a human T cell line promotes cell proliferation/anti-apoptosis of a glioblastoma and two breast cancer cell lines, but inhibits cell proliferation of a colon cancer line. Furthermore, GBP1 reduces radioresistance of two human oral and liver cancer cell lines and correlates with better prognosis in melanoma but with poorer prognosis in human glioblastoma (15)(16)(17)(18)(19)(20)(21), (iii) GBP4 inhibits innate responses to viral infection (22) but lacks known tumor related functions to date. Thus, both knock-down and overexpression of these three genes should be tested in the future experiments to define the exact roles of these proteins within specific contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ICP co-expression network, we searched for potential ICP related genes (ICPRGs) in IFNγ positive tumors that may function as novel ICPs and consequently identified IFI30, GBP1 and GBP4. Based on the identified literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), IFI30, GBP1, and GBP4 suppress mouse primary T cell activation in vitro and mouse innate immune response in vivo while IFI30 and GBP1 appear to increase cell proliferation in a glioma cell line and two breast cancer cell lines but diminish cell proliferation in a colon cancer cell line. Intriguingly, however, IFI30 RNA expression is associated with better patient survival in breast cancer (12) and diffuse large B cell lymphomas (DLBCL) (14) while GPB1 RNA is associated with better patient survival in melanoma (20) but poorer prognosis in human glioblastoma (21).…”
Section: Introductionmentioning
confidence: 99%